Chemistry : an introduction to general, organic, and biological chemistry - Timberlake, Karen C. (Upper Saddle River, New Jersey : Prentice-Hall, 2012)
This chemistry text was written and designed to help you prepare for a career in a health-related profession, such as nursing, dietetics, respiratory therapy, and environmental and agricultural science.